LIFETIME ANALYSIS OF HDPE FLOATING WATER WHEEL AS AN EFFECT OF THERMAL DEGRADATION - Kusumawardhani, Jeanny Marine Ardya Putri Viola; Nugroho, Priyambodo Nur Ardi; Primaningtyas, Widya Emilia (JISO : Journal of Industrial and Systems Optimization, 2023)
The water wheel is an important tool used in cultivating vaname shrimp, which functions as  depositing oxygen in cultivation ponds. HDPE is a polymer material used as a waterwheel float. In outdoor working environment of the waterwheel float in the cultivation pond, which exposed to direct sunlight, resulting in an increase in temperature. The influence of heat from the sun certainly affects to the degradation process of the waterwheel float. In this study, HDPE material was given a variety of heat treatments. The variation of heat given was adjusted to the results of observing field conditions for 1 week where the water wheel was used in the aquaculture pond. The variations of heat treatment given were without treatment, lowest, average, highest temperature heat treatment, and cycles. This research aims to determine the effect of heat on reducing tensile strength, the condition of the functional groups contained, and the service life of the material. The result was a 9% reduction in tensile strength in the samples that were given the highest thermal treatment. Degradation due to thermal effects is proven by the decrease in wave peak intensity for each functional group contained in the HDPE material. Calculation of the estimated service life of the HDPE float must be replaced as fast within 5 months. Kincir air merupakan alat yang penting yang digunakan dalam melakukan budidaya udang vaname, yang berfungsi sebagai alat deposit oksigen pada kolam budidaya. HDPE adalah salah satu material polimer yang digunakan sebagai pelampung kincir air. Lingkungan kerja pelampung kincir air pada kolam budidaya yang terletak di luar ruangan, yang tentunya terpapar matahari langsung, mengakibatkan adanya peningkatan temperatur. Pengaruh panas dari matahari tentunya berpengaruh pada proses degradasi pelampung kincir air. Dalam penelitian ini, material HDPE diberikan variasi perlakuan panas. Variasi panas yang diberikan disesuaikan hasil observasi kondisi lapangan selama 1 minggu di tempat kincir air digunakan pada kolam budidaya. Variasi perlakuan panas yang diberikan yaitu tanpa perlakuan, perlakuan panas temperatur terendah, rata-rata, tertinggi, dan siklus. Penelitian ini memiliki tujuan untuk dapat mengetahui pengaruh panas terhadap penurunan kekuatan tarik, kondisi gugus fungsi yang terkandung, serta umur pakai material. Didapatkan hasil penurunan 9% kekuatan tarik pada sampel yang diberi perlakuan termal tertinggi. Degradasi akibat pengaruh thermal dibuktikan dengan turunnya intensitas puncak gelombang pada tiap-tiap gugus fungsi yang terkandung di dalam material HDPE. Perhitungan perkiraan umur pakai pelampung HDPE paling cepat harus diganti dalam jangka waktu 5 bulan